Visual and Surgical Outcomes in Late Presentation of Retinal Detachment: Doi: 10.36351/pjo.v40i2.1665 - Talpur , Bibi Rafeen; Fariha Sher Wali; Memon, Shahzad; Surhio, Waqas Ali; Younus, Maryam (Pakistan Journal of Ophthalmology, 2024)
Purpose: To evaluate the frequency of treatment success in terms of visual and surgical outcomes in patients with late presentation of retinal detachment. Study Design: Quasi experimental. Place and Duration of Study: Sindh institute of Ophthalmology and visual Sciences from June 2022 to January 2023. Methods: A total of 50 eyes of 50 patients with delayed presentation of retinal detachment who underwent Pars Plana Vitrectomy (PPV) were included and followed up for 6 months. Preand post-surgery Best Corrected Visual Acuity (BCVA) and anatomical attachment of retina were comprehensively analyzed. Factors affecting an atomical success were also studied. Results: Mean age of patients was 47±18 years. Twenty seven patients were (54%) were more than 45 years of age and 32(64%) were males. Thirty eight (76%) patients achieved successful anatomical attachment of retina at 6th month follow-up. Post-operative BCVA also showed improvement in vision.Risk factors identified for poor anatomical and visual outcome following PPV for retinal detachment are; PVR advance stage, longer duration of visual symptoms and poor-presenting BCVA. Age, sex, laterality, Pre-operative BCVA, lens status, diagnosis, and type of surgery showed insignificant associations (P >0.05). Conclusion: Anatomical failure and poor functional outcomes appear to be mostly caused by PVR. PVR, longer duration of visual symptoms and poor-presenting VA are risk factors for poor anatomical and visual outcome following PPV surgery for RD. Late presentations to clinics can decrease with mass awareness. The frequency of proliferative vitreoretinopathy would decline, and visual results would be improved.